The superconducting magnets of the ILC beam delivery system - Parker, B; Anerella, M; Escallier, J; He, P; Jain, A; Marone, A; Nosochkov, Y; Seryi, A (2007)
The ILC Beam Delivery System (BDS) uses a variety of superconducting magnets to maximize luminosity and minimize background. Compact final focus quadrupoles with multifunction correction coils focus incoming beams to few nanometer spot sizes while focusing outgoing disrupted beams into a separate extraction beam line. Anti-solenoids mitigate effects from overlapping focusing and the detector solenoid field. Far from the interaction point (IP) strong octupoles help minimize IP backgrounds. A low-field but very large aperture dipole is integrated with the detector solenoid to reduce backgrounds from beamstrahlung pairs generated at the IP. Physics requirements and magnetic design solutions for the BDS superconducting magnets are reviewed in this paper. ©2007 IEEE.